2022
DOI: 10.3389/fimmu.2022.839362
|View full text |Cite
|
Sign up to set email alerts
|

Energy Metabolism-Related Gene Prognostic Index Predicts Biochemical Recurrence for Patients With Prostate Cancer Undergoing Radical Prostatectomy

Abstract: BackgroundWe aimed to construct and validate an energy metabolism-related gene prognostic index (EMRGPI) to predict biochemical recurrence (BCR) in patients undergoing radical prostatectomy.MethodsWe used Lasso and COX regression analysis to orchestrate the EMRGPI in the TCGA database, and the prognostic value of EMRGPI was further validated externally using the GSE46602. All analyses were conducted with R version 3.6.3 and its suitable packages.ResultsSDC1 and ADH1B were finally used to construct the risk for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 82 publications
0
26
0
Order By: Relevance
“…Activating the immune response to treat cancer has become the cornerstone of modern oncology therapy. Emerging studies have explored the roles of immune cells in PCa [ 65 , 66 ]. Here we showed that Tregs were the most significantly enriched immune cell in the high-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…Activating the immune response to treat cancer has become the cornerstone of modern oncology therapy. Emerging studies have explored the roles of immune cells in PCa [ 65 , 66 ]. Here we showed that Tregs were the most significantly enriched immune cell in the high-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported only chemotherapy response based on MetaGene-signature but lacked immunotherapy response results ( 58 ). Interestingly, studies have shown that signature based on MetaGenes are associated with PCa recurrence undergoing radical prostatectomy ( 59 ). Two other researches also revealed that the model established by MetaGenes can predict the prognosis of PCa, which is consistent with our study ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, active surveillance, radical prostatectomy (RP) or radical radiotherapy (RT), androgen deprivation therapy, and chemotherapy are used to treat PCa, depending on clinical stages, Gleason score, patient performance, and life expectancy [ 3 ]. RP or RT are the preferred approaches for patients with localized PCa, with biochemical recurrence (BCR) occurring in 27%ā€“53% of RP patients and 10ā€“70% of RT patients, respectively [ 4 , 5 ]. Men over the age of 65 are more likely to develop PCa, and by 2050, nearly twice the current population (over 1.5 billion people) will be over the age of 65 [ 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%